The Imaging Performance of Preclinical Ultrasound Scanners Using the Edinburgh Pipe Phantom - Moran, Carmel M; McLeod, Christopher; McBride, Karne; Inglis, Scott; Thomson, Adrian JW; Pye, Stephen D (Frontiers in Physics, 2022)
The greyscale imaging performance of a total of 17 preclinical transducer/scanner combinations were measured over a period of 10 years. These comprised nine single element transducers and eight array transducers with nominal central frequencies ranging between 15MHz and 55MHz, and were from four commercially-available preclinical ultrasound scanners. Performance was assessed using a single figure of merit, the resolution integral, using measurements acquired from images of a test-object, the Edinburgh Pipe Phantom. Two further parameters were derived from the resolution integral: characteristic resolution and depth-of-field. Our results demonstrate that (1) resolution integral values of the array transducers were greater than single-element transducers, and (2) single element transducers demonstrated smaller depths of field than array transducers of the same nominal frequency.